2003
DOI: 10.1152/ajpendo.00307.2002
|View full text |Cite
|
Sign up to set email alerts
|

Human osteoblast-like cell proliferation induced by calcitonin-related peptides involves PKC activity

Abstract: The calcitonin peptides [calcitonin (CT), calcitonin gene-related peptide (CGRP), amylin] share many biological actions, including activity on bone cells. In the present study, CT (10−11 to 10−9 M) stimulated [3H]thymidine incorporation in primary cultures of human osteoblasts (hOB), as already demonstrated for CGRP and amylin. RT-PCR analysis showed that the calcitonin receptor and the calcitonin receptor-like receptor are both expressed in hOB. In these cells, CT (10−10 M) and amylin (10−9 M), in contrast to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
49
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 42 publications
1
49
0
Order By: Relevance
“…Although previous study has shown the activation of PKC by CGRP in osteoblast cells (38), our study is the first to clarify that the PKC⑀ subtype is selectively activated by CGRP in alveolar epithelial cells. Further studies are warranted to elucidate whether the CGRP/PKC⑀/HSP70 pathway also plays a role in the effect of CGRP in other cell types, especially the endothelial cells, cardiac myocytes, and neurons.…”
Section: Discussionmentioning
confidence: 61%
“…Although previous study has shown the activation of PKC by CGRP in osteoblast cells (38), our study is the first to clarify that the PKC⑀ subtype is selectively activated by CGRP in alveolar epithelial cells. Further studies are warranted to elucidate whether the CGRP/PKC⑀/HSP70 pathway also plays a role in the effect of CGRP in other cell types, especially the endothelial cells, cardiac myocytes, and neurons.…”
Section: Discussionmentioning
confidence: 61%
“…3,19, and 28; Burns and Kawase, unpublished observations). In addition, we (18,20,21) and others (11,12,38,39) have recently reported that CGRP can stimulate cAMP-independent intracellular signaling pathways in several osteoblastic cell types. We thought it significant that mature osteoblast-like cells respond to CGRP by increasing intracellular Ca 2ϩ ([Ca 2ϩ ] int ) and/or altering membrane potential (E m ) while yielding small increases (if any) in cAMP production (18,20,21).…”
mentioning
confidence: 67%
“…BMP-2 promotes the proliferation of pre-osteoblast cells, induces the osteogenic or chondrogenic differentiation of mesenchymal cells [17,18] , and improves the osteogenic phenotype and capacity of stem cells through increased ALP activity and osteocalcin mRNA expression. Signal transduction studies have revealed that the Smad and P38MAPK pathways are immediately downstream of BMP receptors and that they play central roles in BMP signal transduction [4,[19][20][21] .…”
Section: Introductionmentioning
confidence: 99%